Validity and reliability: Social attitude assessment instruments - Bambang Yuniarto; Rivo Panji Yudha; Aulia Sholichah Iman Nurchotimah (Communications in Humanities and Social Sciences, 2022)
The purpose of this study is to develop an instrument for assessing social attitude competence whose constructs are valid according to experts and empirically valid and reliable based on field trials in Civics learning for high school students. This research was conducted through a quantitative descriptive approach at SMP Negeri 1 Gebang. Social attitude assessment instrument was used and it contained 28 items and an expert validation observation sheet. Design validation was done by reviewing the product design by three experts (expert judgment). The study was conducted to determine the feasibility of the instrument from the aspect of substance, construction, and language of the social attitude assessment instrument. Advice was given by experts after doing research to get approval, which was later used as a benchmark to state that the product was logically valid. The measurement of the content validity of social attitude statements was conducted using Likert scale and the reliability test used the Rasch Model approach. The results of the field test showed that the social attitude assessment instrument was valid in terms of content and constructs. The reliability test using the Rasch model approach showed that the product reliability was categorized as satisfactory. The final product is considered suitable for direct use by teachers and can be further developed with grid references.